SIMULASI LINTASAN UJI SIM SEBAGAI EDUKASI KEAMANAN DAN KETERTIBAN BERKENDARA DI DESA KALISAT KECAMATAN REMBANG KABUPATEN PASURUAN - Budiati, Anik; Choiruddin, Muhammad; Putri Arnita, Ni Putu (LPPM Universitas Bhayangkara Surabaya, 2024)
Kalisat Village is a residential area dominated by large areas of empty land as vacant land. Kalisat Village itself has the potential to be developed as a place for driving license test track simulations. The SIM Test Track Simulation is an educational tour to test driving skills and understanding of traffic signs so that people, especially children, understand and understand traffic rules and can apply them to their daily lives. Traffic violations are the things that most often occur on highways, traffic problems are alsoregulated in Law No. 22 of 2009 which explains the movement of vehicles and people in road traffic spaces.